Bifunctional electrocatalyst and preparation method thereof and application in zinc-air battery
By using the steps of electrodeposition, ion replacement and pyrolysis in the cathode catalyst of zinc-air batteries, the problems of slow kinetics, high cost and insufficient durability of cathode catalysts in the prior art are solved, and more efficient and stable catalytic performance is achieved.
Patent Information
- Application Number
- CN202410327021.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-21
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-03-21
AI Technical Summary
The cathode catalyst ORR of existing zinc-air batteries has slow kinetics, high production cost, insufficient durability and low stability.
The three-electrode system is used to electrodeposiate hydroxide on the conductive substrate, and the transition metal is loaded by ionic replacement, followed by reaction in tri(hydroxymethyl)aminomethane and dopamine hydrochloride solution, and pyrolysis is carried out under an inert atmosphere to obtain a bifunctional electrocatalyst with a feather nanosheet array structure similar to that of feather nanosheets.
The ORR half-wave potential and starting potential of the dual-function electrocatalyst are improved, catalytic performance is enhanced, cost is reduced, and material stability and cycle life are improved.
Smart Images

Figure CN118073585B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a bifunctional electrocatalyst and a preparation method thereof and application in a zinc-air battery, belonging to the technical field of preparing a bifunctional electrocatalyst for a zinc-air battery by an ion replacement method. Background Art
[0002] In recent years, car battery explosions have been common. Lithium-ion batteries are prone to lithium dendrites, which can cause battery short circuits and explosions. In addition, lithium-ion batteries have a low specific energy density (200 Wh / kg), so a battery with strong safety and high specific energy density is needed to replace them. Aqueous zinc-air batteries are a new type of environmentally friendly and pollution-free energy because their positive electrode reactant is oxygen in the air.
[0003] At present, zinc-air batteries are widely used in hearing aids. The cathode catalyst of commercial zinc-air batteries is 20% Pt / C, which has problems such as high production cost and insufficient durability. Non-precious metal catalysts have always attracted widespread attention due to their low cost and high durability. However, current non-precious metal catalysts have problems such as unstable adsorption with oxygen intermediates and high impedance, which lead to slow ORR kinetics. In addition, the preparation of powder catalysts requires binders, which makes the catalyst easy to fall off and unstable. The preparation of simple and efficient cathode catalysts has always been the focus and challenge of people's research. Summary of the invention
[0004] In order to solve the problems of slow ORR kinetics, high production cost, insufficient durability and low stability of cathode catalysts of existing zinc-air batteries, the present invention provides a bifunctional electrocatalyst and a preparation method thereof and application in zinc-air batteries.
[0005] The technical solution of the present invention:
[0006] One of the purposes of the present invention is to provide a method for preparing a bifunctional electrocatalyst, the method comprising the following steps:
[0007] (1) A three-electrode system is used, a nitrate solution is used as an electrolyte, and a chronopotentiometry method is used to electrodeposit hydroxide on a conductive substrate to obtain a metal hydroxide-carbon cloth composite;
[0008] (2) immersing the metal hydroxide-carbon cloth composite in a divalent transition metal salt solution to perform ion replacement to obtain a metal hydroxide-carbon cloth composite loaded with a transition metal;
[0009] (3) Immersing the metal hydroxide-carbon cloth composite loaded with transition metal into a tris(hydroxymethyl)aminomethane solution, then adding a dopamine hydrochloride solution and stirring the mixture at room temperature. After the reaction, the product is washed and dried, and then pyrolyzed in an inert atmosphere to obtain a bifunctional electrocatalyst.
[0010] It is further defined that the conductive substrate in (1) is pretreated before use, and the pretreatment method is: the conductive substrate is boiled in ethanol for 20 minutes, then washed three times with deionized water, then placed in HCl solution for ultrasonic treatment for 30 minutes, and finally placed in water for ultrasonic treatment until the pH is neutral.
[0011] It is further defined that the conductive substrate in (1) is carbon paper, carbon felt cloth, nickel foam or copper foam.
[0012] Further definition, the three-electrode system in (1) is: platinum sheet, CoO-Ni / C@C and standard hydrogen electrode are counter electrode, working electrode and reference electrode respectively; the metal ion in the nitrate solution is Co 2+ 、Ni 2+ , Mn 2+ , Cu 2+ One or two of the above; the concentration of the nitrate solution was 0.1 mol / L; during the electrodeposition process, a constant potential of -1.0 V vs. SHE was set, and the electrodeposition time was 1200 s.
[0013] It is further defined that the nitrate solution is a Co(NO3)2 solution.
[0014] It is further defined that the concentration of the divalent transition metal salt solution in (2) is 0.1 mol / L; and the ion exchange conditions are: stirring at 260 rpm for 100 min.
[0015] It is further defined that the divalent transition metal salt solution is a Ni(NO3)2 solution.
[0016] It is further defined that the concentration of the tris(hydroxymethyl)aminomethane solution in (3) is 2.5 g / L; the concentration of the dopamine hydrochloride solution is 6.25 mg / mL; and the volume ratio of the tris(hydroxymethyl)aminomethane solution to the dopamine hydrochloride solution is 5:4.
[0017] It is further defined that the reaction speed of stirring at room temperature in (3) is 230 rpm and the time is 6 h.
[0018] It is further defined that the pyrolysis in (3) is carried out under N2 atmosphere with a gas flow rate of 50 mL / min, a heating rate of 5°C / min, a pyrolysis temperature of 800°C and a time of 1 h.
[0019] The second object of the present invention is to provide a bifunctional electrocatalyst prepared by the above method, wherein the bifunctional electrocatalyst is composed of a uniformly arranged feather-like nanosheet array shape, and the thickness of the nanosheet is 180~200 nm.
[0020] The third object of the present invention is to provide an application of the above-mentioned bifunctional electrocatalyst, specifically as an air electrode catalyst of a zinc-air battery.
[0021] Beneficial effects:
[0022] The present invention uses a cobalt nitrate solution as an electrodeposition electrolyte on a conductive substrate to deposit a metal hydroxide array, and then uses a divalent transition metal salt as an ion replacement source to further enhance the bifunctional catalytic performance through ion replacement, and finally forms a "feather-like" bifunctional electrocatalyst through carbonization. Compared with the prior art, the present invention also has the following advantages:
[0023] (1) The present invention uses carbon cloth as a conductive substrate, which has good conductivity and avoids poor performance caused by conductivity problems. In addition, a microscopic array is constructed on the carbon cloth by in-situ growth, making the arrayed catalyst more secure and can be directly used as a battery electrode, avoiding the adverse effects of the binder used in the electrode preparation process.
[0024] (2) The bifunctional electrocatalyst prepared by the present invention has a unique feather-like nanosheet array structure with a nanosheet thickness of about 200 nm. The unique structure makes the catalyst more stable while increasing the specific surface area, exposing more active sites and promoting electrocatalytic performance.
[0025] (3) The present invention uses an ion exchange method, and the exchange of divalent transition metal ions further enhances the bifunctional catalytic performance of the material, so that the ORR half-wave potential of the bifunctional electrocatalyst reaches 0.82 V and the onset potential reaches 0.92 V.
[0026] (4) The preparation method of the bifunctional electrocatalyst provided by the present invention is simple, the process is stable, the repeatability is high, and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 SEM photos of Co(OH)2@CC prepared in Example 1 (different magnifications);
[0028] Figure 2 SEM photos of Co(OH)2-Ni@CC prepared in Example 1 (different magnifications);
[0029] Figure 3 SEM photos of CoO-Ni / C@CC prepared in Example 1 (different magnifications);
[0030] Figure 4 This is the X-ray diffraction pattern of CoO-Ni / C@CC prepared in Example 1;
[0031] Figure 5 CV test result diagram of oxygen reduction performance of CoO-Ni / C@CC prepared in Example 1;
[0032] Figure 6 This is a graph showing the LSV test results of the oxygen reduction performance of CoO-Ni / C@CC prepared in Example 1;
[0033] Figure 7 This is a LSV test result diagram of the oxygen evolution performance of CoO-Ni / C@CC prepared in Example 1;
[0034] Figure 8 This is a graph showing the charge and discharge cycle stability test results of the zinc-air battery prepared in Example 1. DETAILED DESCRIPTION
[0035] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0036] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0037] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0038] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0039] Embodiment 1:
[0040] The method for preparing the CoO-Ni / C@CC bifunctional electrocatalyst in this embodiment includes the following steps:
[0041] Step 1: Pretreatment of carbon cloth: Boil 2×4 cm carbon cloth in ethanol for 20 min, wash it three times with deionized water to remove organic matter on the surface, and then ultrasonically treat the carbon cloth in 1 M HCl solution for 30 min. Use water as the washing liquid to ultrasonically wash away the acid until the pH value is 7.0 to further remove surface impurities and improve surface hydrophilicity.
[0042] Step 2: Place the pretreated carbon cloth in a three-electrode system, with platinum sheet, CoO-Ni / C@C and standard hydrogen electrode as counter electrode, working electrode and reference electrode respectively, 0.1 M Co(NO3)2 as electrolyte, and use chronopotentiometry to set a constant potential of -1.0 V vs. SHE. Electrodeposition was performed for 1200 s to obtain Co(OH)2@CC.
[0043] The microstructure of the prepared Co(OH)2@CC was characterized. Figure 1 As shown by Figure 1 It can be seen that the Co(OH)2 after electrodeposition is a lamellar structure, and the Co(OH)2 lamellar layers supported by the carbon cloth are interlaced with each other.
[0044] Step 3, ion replacement: prepare 80 mL of 0.1 M Ni(NO3)2 solution, and place Co(OH)2@CC in the Ni(NO3)2 solution and stir at 260 rpm for 100 min to obtain Co(OH)2-Ni@CC.
[0045] The microstructure of the prepared Co(OH)2-Ni@CC was characterized. Figure 2 As shown by Figure 2 It can be seen that after the ion replacement of Ni, the Co(OH)2 sheets have a macroporous structure and the interlaced morphology of the sheets is basically maintained.
[0046] Step 4: Coating dopamine carbon layer: Dissolve 250 mg of tris(hydroxymethyl)aminomethane in 100 mL of water, dissolve 500 mg of dopamine hydrochloride in 80 mL of water, and then immerse Co(OH)2-Ni@CC in tris(hydroxymethyl)aminomethane for 5 min, then pour the dopamine hydrochloride solution into the tris(hydroxymethyl)aminomethane solution, and stir at 230 rpm for 6 h. After stirring, wash three times with deionized water and once with ethanol, and finally dry overnight at 60°C to obtain Co(OH)2-Ni / PDA@CC.
[0047] Step 5. Pyrolysis: Under N2 atmosphere, Co(OH)2-Ni / PDA@CC was pyrolyzed with a gas flow rate of 50 mL / min, a heating rate of 5°C / min, a pyrolysis temperature of 800°C, and a pyrolysis time of 1 h to obtain CoO-Ni / C@CC bifunctional electrocatalyst.
[0048] The microstructure of the prepared CoO-Ni / C@CC was characterized using a Hitachi SU8010 scanning electron microscope. Figure 3 As shown by Figure 3 It can be seen that Co(OH)2-Ni / PDA@CC has a unique "feather-like" nanosheet array structure with a nanosheet thickness of about 200 nm.
[0049] The prepared CoO-Ni / C@CC was further analyzed by X-ray diffractometer. Figure 4 As shown by Figure 4 It can be seen that the sharp peak at 26.1° of the sample belongs to the (002) crystal plane of carbon, indicating that it is crystalline carbon, indicating the successful coating of the carbon layer. At the same time, the three narrow diffraction peaks at 31.6°, 42.4° and 62.5° are respectively attributed to the (101), (110) and (002) crystal planes of CoO (PDF#65-5474), indicating that the CoO phase is formed during the pyrolysis process. In addition, the three narrow diffraction peaks at 44.2°, 51.5° and 75.8° correspond to the (111), (200) and (220) crystal planes of metal Co (PDF#15-0806) and the (111), (200) and (220) crystal planes of metal Ni (PDF#65-0380), indicating that the Co and Ni species are reduced and aggregated to form a CoNi alloy phase during the pyrolysis process.
[0050] The electrical properties of the prepared CoO-Ni / C@CC were characterized:
[0051] (1) The electrode oxygen reduction performance of CoO-Ni / C@CC was tested using an electrochemical workstation (CHI760E).
[0052] In 1 M KOH electrolyte, a three-electrode system was used, with CoO-Ni / C@CC as the working electrode, a standard hydrogen electrode as the reference electrode, and a platinum sheet as the counter electrode. The potential range was set to 1.2 V to -0.1 V, and the scan rate was 100 mV / s. The CV test was performed, and the results are shown in Figure 2. Figure 5 As shown by Figure 5 It can be seen that at 0.80 V, an oxygen reduction peak appears in the CoO-Ni / C@CC electrode material, indicating that the prepared self-supporting catalyst has excellent ORR activity.
[0053] (2) The electrode oxygen reduction performance of CoO-Ni / C@CC was tested using an electrochemical workstation (CHI760E). In 1 MKOH electrolyte, a three-electrode system was used, with CoO-Ni / C@CC as the working electrode, a standard hydrogen electrode as the reference electrode, and a platinum sheet as the counter electrode. The potential range was set to 1.2 V to -0.1 V, and the scan rate was 5 mV / s. The LSV test was performed. The test results showed that its half-wave potential reached 0.82 V and the starting potential reached 0.92 V. Figure 6 shown.
[0054] (3) The electrode oxygen evolution performance of CoO-Ni / C@CC was tested using an electrochemical workstation (CHI760E).
[0055] In 1 M KOH electrolyte, a three-electrode system was used, with CoO-Ni / C@CC as the working electrode, a standard hydrogen electrode as the reference electrode, and a platinum sheet as the counter electrode. The potential range was set to 0.9 V to 2.1 V, and the scan rate was 10 mV / s to perform the LSV test. Figure 7 As shown, at 50 mA / cm 2 The overpotential reaches 440 mV at a current density of 2.54 Å, indicating that it has good OER performance.
[0056] (4) The CoO-Ni / C@CC prepared in this example was used to assemble a zinc-air battery, specifically using a zinc sheet as the negative electrode, CoO-Ni / C@CC as the positive electrode catalyst, and 6 M KOH containing 0.2 M Zn(OAc)2 as the electrolyte. The performance of the zinc-air battery was tested on the CoO-Ni / C@CC catalyst using the Blue Electric test system, with a current density of 2 mA / cm 2 The charging time is 5 min and the discharging time is 5 min. The battery has a long-term charge and discharge cycle stability. Figure 8 As shown in the figure, the charge-discharge potential difference did not decay significantly after cycling for nearly 700 h, indicating that the catalyst has good cycle stability.
[0057] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing a bifunctional electrocatalyst, characterized in that: The steps include: (1) A three-electrode system is used, a nitrate solution is used as an electrolyte, and a chronopotentiometry method is used to electrodeposit hydroxide on a conductive substrate to obtain a metal hydroxide-carbon cloth composite; The metal ion in the nitrate solution is Co 2+ ; (2) immersing the metal hydroxide-carbon cloth composite in a divalent transition metal salt solution to perform ion replacement to obtain a metal hydroxide-carbon cloth composite loaded with a transition metal; The divalent transition metal salt solution is Ni(NO3)2 solution; (3) immersing the metal hydroxide-carbon cloth composite loaded with transition metal into a tris(hydroxymethyl)aminomethane solution, then adding a dopamine hydrochloride solution, stirring the reaction at room temperature, washing and drying the product after the reaction, and then pyrolyzing the product under an inert atmosphere to obtain a bifunctional electrocatalyst; The pyrolysis was carried out under N2 atmosphere with a gas flow rate of 50 mL / min, a heating rate of 5°C / min, a pyrolysis temperature of 800°C, and a time of 1 h; The obtained bifunctional electrocatalyst is composed of a uniformly arranged feather-like nanosheet array with a thickness of 180~200 nm.
2. The preparation method according to claim 1, characterized in that: The conductive substrate in (1) was pretreated before use. The pretreatment method was as follows: the conductive substrate was boiled in ethanol for 20 min, then washed three times with deionized water, then ultrasonically treated in HCl solution for 30 min, and finally ultrasonically treated in water until the pH was neutral.
3. The preparation method according to claim 1, characterized in that: (1) The three-electrode system is as follows: platinum sheet, CoO-Ni / C@C and standard hydrogen electrode are used as counter electrode, working electrode and reference electrode respectively; the concentration of nitrate solution is 0.1 mol / L; during the electrodeposition process, a constant potential of -1.0 V vs. SHE is set, and the electrodeposition time is 1200 s.
4. The preparation method according to claim 1, characterized in that: (2) The concentration of the divalent transition metal salt solution was 0.1 mol / L; the ion exchange conditions were: stirring at 260 rpm for 100 min.
5. The preparation method according to claim 1, characterized in that: (3) The concentration of the tris(hydroxymethyl)aminomethane solution is 2.5 g / L; the concentration of the dopamine hydrochloride solution is 6.25 mg / mL; and the volume ratio of the tris(hydroxymethyl)aminomethane solution to the dopamine hydrochloride solution is 5:
4.
6. The preparation method according to claim 1, characterized in that: (3) The reaction was stirred at room temperature at a speed of 230 rpm for 6 h.
7. An application of a bifunctional electrocatalyst prepared by the method according to claim 1, characterized in that: Used in zinc-air batteries, it has ORR / OER bifunctional catalytic activity.
Citation Information
Patent Citations
Preparation method of platinum-doped modified cobalt-based catalyst
CN116099566A